2004
DOI: 10.1002/pmic.200300580
|View full text |Cite
|
Sign up to set email alerts
|

Database search post‐processing by neural network: Advanced facilities for identification of components in protein mixtures using mass spectrometric peptide mapping

Abstract: Database search post-processing by neural network was employed in peptide mapping experiments. The database search was performed using both the known algorithms and score functions, such as Bayesian, MOWSE, Z-score, correlations between calculated and actual peptide length fractional abundance, and, in addition, the probability of protein digest pattern in peptide fingerprint, all embedded in locally developed program. The new signal-processing algorithm based on neural network improves signal-noise separation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…According to Lokhov et al (2004) and Lisitsa et al (2010), a mixture of 2-5 proteins was commonly observed in the SDS-PAGE slice band when analysed using peptide mass fingerprinting. Similar results were also observed by Petushkova et al (2012): separation of protein by SDS-PAGE resulted in more than one protein per gel band.…”
Section: Resultsmentioning
confidence: 99%
“…According to Lokhov et al (2004) and Lisitsa et al (2010), a mixture of 2-5 proteins was commonly observed in the SDS-PAGE slice band when analysed using peptide mass fingerprinting. Similar results were also observed by Petushkova et al (2012): separation of protein by SDS-PAGE resulted in more than one protein per gel band.…”
Section: Resultsmentioning
confidence: 99%
“…the SDS-PAGE lane is cut into slices whereupon the protein content of each slice is analyzed by MS method [2,3,7]. Analysis of obtained slices by peptide mass fingerprinting (PMF) has shown that each slice often appears to be a mixture of 2 to 5 proteins [2,10]. Mixed spectra impeded identification, which necessitated the development of additional functions for the software; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The probability of identification was shown by the MOWSE score [20] and the sequence alignment was achieved by the T-COFFEE program [21]. …”
Section: Methodsmentioning
confidence: 99%